Regional competition in the eastern Mediterranean and its impact on the strategic balance of the region - Assestant Prof, Dr. Baqer Jawad Kadhim (Tikrit Journal For Political Science, 2024)
The Eastern Mediterranean region is one of the most important areas for the current trends of many influential forces for different considerations, especially since many studies indicate that this region will be a focus of conflict between the major powers in the coming period, which is what pushed those forces to strengthen their presence in the region, and the growth of policy Creating new allied groups and axes in it, and consider it as a new arena for influence and regional competitions, which was echoed in changing the rules of the strategic balance equation in the region.